Power Dynamics and Cultural Clashes in Doris Lessing’s The Grass Is Singing: Decolonising the Discourse of Differences - Islam, Rama (The Outlook: Journal of English Studies, 2024)
This paper examines the power dynamics and cultural clashes in Doris Lessing’s The Grass Is Singing, focusing on the interactions between the white protagonist, Mary Turner, and her black servants Samson and Moses, as well as a white servant Tony. Set in colonial Southern Rhodesia (today Zimbabwe), the novel portrays the pervasive racism and superiority complex of the white colonialists. Mary’s negative perceptions of black culture highlight the colonialists’ failure to appreciate indigenous traditions, reinforcing unequal power structures. Drawing attention to theoretical frameworks such as Franz Fanon’s concept of anti-racism and Ngugi wa Thiang’o’s theory of decolonisation, this paper examines Moses’s resistance to oppression and his quest for decolonisation as manifestations of individual agency within imperialism. Moses’ journey toward decolonisation symbolises a broader struggle for psychological, cultural, and economic liberation from colonial oppression. This analysis underscores the complexities of authority and resistance, illustrating how Mary’s attitudes inadvertently trigger Moses’s decolonisation process. This paper contributes to a deeper understanding of Lessing’s exploration of colonial authority, cultural differences, and the necessity of decolonisation.